2013
DOI: 10.1186/1471-2261-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a self-management patient education program for patients with chronic heart failure undergoing inpatient cardiac rehabilitation: study protocol of a cluster randomized controlled trial

Abstract: BackgroundChronic heart failure requires a complex treatment regimen on a life-long basis. Therefore, self-care/self-management is an essential part of successful treatment and comprehensive patient education is warranted. However, specific information on program features and educational strategies enhancing treatment success is lacking. This trial aims to evaluate a patient-oriented and theory-based self-management educational group program as compared to usual care education during inpatient cardiac rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…Subsequently, all therapeutic regimens need careful awareness, interpretation and positive attitudes from patients. [25,28] This is goes in line with Rankin S., in 2002, who clarified that patient literacy, inner motivation and a positive attitude regarding self-care management of their own health and illness care is considered a foundation of health-care management. Nurses should focus on helping them to acquire all skills, attitudes or knowledge needed to manage health complaints accurately.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Subsequently, all therapeutic regimens need careful awareness, interpretation and positive attitudes from patients. [25,28] This is goes in line with Rankin S., in 2002, who clarified that patient literacy, inner motivation and a positive attitude regarding self-care management of their own health and illness care is considered a foundation of health-care management. Nurses should focus on helping them to acquire all skills, attitudes or knowledge needed to manage health complaints accurately.…”
Section: Discussionsupporting
confidence: 59%
“…Consequently, self-care management is an essential part to be learned by this group of patients for successful treatment. [3,24,25] Patient health education is proposed to promote self-care management of patients with CHF. There are specific educational techniques which help patients in attaining their wishes through well planned self-care management educational programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,24 Specialist CHF outpatient programmes have yet to demonstrate an improvement in patient adherence compared to rates achieved in primary care. 25 A small number of studies have observed benefits of group self-management interventions in other chronic disease settings, such as diabetes; 26,27 however, the active component/s driving success of these programmes is unknown.…”
Section: Recommendations To Promote Patient Self-management: a Socialmentioning
confidence: 99%